Miller-Fisher syndrome presenting with headache and ophthalmoparesis: a case report and literature review - Huang, Jin; Lin, Lingling; Huang, Xuerong; Yan, Xiaoxiao (Frontiers in Medicine, 2025)
Miller-Fisher syndrome (MFS) is a rare variant of Guillain-Barre syndrome, classically characterized by a triad of symptoms, including ataxia, areflexia, and ophthalmoplegia. However, only a few cases have documented clinical data on a rare atypical presentation of MFS, with headache and ophthalmoplegia as the initial manifestation. We report an 83-year-old Chinese female patient with no history of respiratory or gastrointestinal infection presented with headache and ophthalmoplegia. Cerebrospinal fluid analysis showed albuminocytological dissociation, along with positive anti-GQ1b antibodies, leading to a diagnosis of incomplete Miller-Fisher syndrome. The patient’s headache symptoms were relieved following immunoglobulin treatment, and ophthalmoplegia resolved within 20 days. A literature search identified eight cases of MFS patients initially presenting with headaches, followed by ophthalmoplegia. Detection of anti-ganglioside antibodies in serum or cerebrospinal fluid enables early diagnosis of MFS, and early immunoglobulin treatment improves patient prognosis.